Leading language programs in a changing world an ecological approach - Pennington, Martha Carswell; Hoekje, Barbara Jean. (Bingley, UK : Emerald, 2010)
Leading Language Programs in a Changing World: An Ecological Model presents a comprehensive view of management and leadership in language programs as situated in a complex, globalized context with rapidly changing characteristics. The language program is described as an extensive ecology made up of many different types of interacting parts, which leaders of these programs must manage and balance with strong attention to context and to the future. The discussion emphasizes the complexity of the job of leading a language program and the many types of roles the leadership must fill in monitoring the program and its context for continuity and change and leading with an eye to the future. The focus is on college and university English language programs, with discussion of the place they occupy within academia and in relation to other types of language programs (e.g. foreign language and English composition). The book is both practical and theoretical, offering case studies and overviews of "nuts and bolts" issues of administration such as financial, data, and people management, in addition to an original model that problematizes and theorizes the language program based on notions of ecology and frames, a review of research, and suggestions for further research.
Preface / Martha C. Pennington and Barbara J. Hoekje -- The language program in a changing world / Martha C. Pennington and Barbara J. Hoekje -- The language program ecology / Martha C. Pennington and Barbara J. Hoekje -- Situating the language program / Martha C. Pennington and Barbara J. Hoekje -- The students / Martha C. Pennington and Barbara J. Hoekje -- The faculty / Martha C. Pennington and Barbara J. Hoekje -- The leadership / Martha C. Pennington and Barbara J. Hoekje -- Curriculum development / Martha C. Pennington and Barbara J. Hoekje -- Program development / Martha C. Pennington and Barbara J. Hoekje -- Leading into the future / Martha C. Pennington and Barbara J. Hoekje.
Description based on print version record.
Keywords: English language -- Study and teaching (Higher) -- Foreign speakers; Second language acquisition; ELT: teaching theories & methods; ELT resource books for teachers; Language Arts & Disciplines -- Study & Teaching; Foreign Language Study -- English as a Second Language